2016
DOI: 10.1002/hbm.23124
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain correlates of cognitive and behavioral impairment in MND

Abstract: Cortical thinning and WM degeneration are highly associated with neuropsychological and behavioral symptoms in patients with MND. DT MRI metrics seem to be the most sensitive markers of extra-motor deficits within the MND spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
74
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 71 publications
11
74
1
2
Order By: Relevance
“…This is consistent with previous studies supporting the notion that the right hemisphere has a critical role in complex social behaviours 5 25 26. It is interesting to note that the right superior frontal gyrus involvement has been found in motor neuron disease with comorbid FTD,27 suggesting that its early involvement in patients with ALS might be marker for the development of bvFTD.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies supporting the notion that the right hemisphere has a critical role in complex social behaviours 5 25 26. It is interesting to note that the right superior frontal gyrus involvement has been found in motor neuron disease with comorbid FTD,27 suggesting that its early involvement in patients with ALS might be marker for the development of bvFTD.…”
Section: Discussionmentioning
confidence: 99%
“…DTI metrics have consistently demonstrated significant white matter alterations in the corticospinal tracts (CSTs) in ALS compared with healthy controls, reporting reduced FA [4250] and increased MD and RD [51, 52]. DTI studies have specifically noted altered indices in the corpus callosum in ALS [5355], as well extensive extramotor white matter involvement [5658]. Asymptomatic carriers of pathogenic mutations in SOD1 were also reported to have lower FA in the CSTs [59], though a result not replicated in a subsequent study [60].…”
Section: Emerging Imaging Biomarkers In Alsmentioning
confidence: 99%
“…Furthermore, surface-based analysis of the precentral gyrus revealed that compared with patients with ALS, patients with a UMN phenotype displayed reduced cortical thickness [70]. The involvement of extramotor cortical regions is more severe in patients with ALS with cognitive impairment and ALS-FTD [58]. …”
Section: Emerging Imaging Biomarkers In Alsmentioning
confidence: 99%
“…Even less evidence exists of the imaging alterations observed in non-demented patients with ALS but with mild cognitive impairment. Recently, Agosta et al, in a study with DTI, demonstrated the association of the degeneration of white matter tracts with neuropsychological deficits in patients with ALS 22 . In our study, we highlight that all patients were evaluated at an early stage of the disease with a full battery of neuropsychological tests adapted to ALS patients, which included all cognitive areas.…”
Section: Discussionmentioning
confidence: 99%